Can data collected in the Citizen Science project EduMar be used to monitor coastal marine biodiversity in Portugal? - Luís, C. (2019)
In a climate change scenario, it is important to aware society for the need to protect marine species biodiversity and to ensure its sustainability. Therefore, the project EduMar/EduSea (Educate for the Sea) is being developed in Portugal aiming to educate students (elementary and middle school) for the preservation of the sea and its resources through citizen science. More than 300 students are participating in a set of interdisciplinary science activities focusing on learning the causes and consequences of climate change in ecosystems of the intertidal rocky shores and acquiring skills to identify and report on site a set of bio-indicator and common rocky shores species. At Avencas Beach, Portugal, using the iNaturalist app, students are mapping those species, gathering data to help researchers better monitoring the coastal marine biodiversity and understanding how climate change may affect that biodiversity. We will present data collected by these students analysing its quality for research purposes. We will also share our experience with such young citizen scientists and the best practices learned for future design of similar projects.